Analysis of the Impact of Economic Growth and Deforestation Rates on Carbon Dioxide Emissions in Indonesia - Joko Hadi Susilo; Hartiningsih Astuti; Sutrisno; Defi Tristio Putri; Dwi Irnawati; Selvia Dwi Safitri (Universitas Negeri Semarang, 2026)
Indonesia faces the challenge of maintaining a balance between economic growth and environmental sustainability, particularly regarding rising carbon dioxide (CO₂) emissions. However, studies that simultaneously integrate the effects of economic growth and deforestation rates on carbon emissions remain relatively limited. This study aims to address this gap by analyzing the effects of economic growth and deforestation rates on CO₂ emissions in Indonesia. Using annual time-series data from 2004 to 2023, this study applies the Error Correction Model (ECM) approach to evaluate the short-term and long-term relationships among the variables. The results indicate that, individually, economic growth and deforestation rates do not have a significant effect on CO₂ emissions in either the short or long term. However, when considered simultaneously, both variables have a significant long-term impact on CO₂ emissions. These findings suggest that carbon emission dynamics in Indonesia are influenced not only by economic activities and land-use changes but also by other factors outside the model. This study offers important implications for the government in formulating sustainable development policies, particularly through deforestation control and the strengthening of the transition to environmentally friendly energy.